Feminism as a trigger for change in the dynamics of Danjyo Kankei and the unmarried trend in Japan - Awalia Dhia Nisrina; Rahma Sintya Devi; Dina Pasya Surayya; Rahma Ning Tias; Grace Evelyn Turnip; Septyanto Galan Prakoso (An-Nisa’ Journal of Gender Studies, 2024)
In the Japanese patriarchal system, the male head of the household holds absolute decision-making power, and women are expected to obey all such decisions. The unmarried trend is also widely experienced by men, not only by women. This study aims to analyze how the introduction of feminism has transformed the dynamics of Danjyo Kankei (gender relations) and triggered the unmarried trend in Japan. A qualitative approach was employed, using primary data from Japanese government statistics and secondary data from the literature. Thematic analysis was conducted to identify patterns of feminism, gender relations, and the unmarried trend. The study reveals: (1) The unmarried trend in Japan has intensified, marked by a delay in the age at marriage, a high proportion of the single population, and a decline in birth rates due to changing social values, economic pressures, and rising individualism. (2) Feminism has transformed Japanese gender relations from ie patriarchy toward equality. Policies that strengthen women’s economic independence have enabled women to freely choose unmarried status as a form of autonomy and resistance. The study concludes that the transformation of gender relations and the unmarried trend in Japan are interrelated as outcomes of feminist change. Feminism deconstructs ie patriarchy through education and economic independence, making unmarried status a rational strategy in response to economic pressures and gender inequality. This study reinforces feminist constructivism by demonstrating that patriarchy operates through cultural, economic, and familial mechanisms, and emphasizes the importance of structural policies and more equitable, autonomous spaces for individual life choices.